PENDIDIKAN ANAK PRANATAL MENURUT AJARAN ISLAM - Armin Ibnu Rasyim; Halimatus Syadi’yah (E-Jurnal Aksioma Ad-Diniyyah : The Indonesian Journal of Islamic Studies, 2013)
This study aims to determine the child's prenatal education in Islam. This research approach or research literature. While writing method using hermeneutic methods results in this study were: 1) prenatal child education in Islam at a psychological aspect to include; establish the prayer, reading the Qur'an, and pray always, in this way will affect the child for worship an Islamic, 2) children prenatal education in Islam at the physical aspects can include: eating a nutritious diet and exercise properly, the way it will affect the growth and development of children well, and 3) children prenatal education in Islam the psychological and emotional aspects can include: noble, attend lectures, choosing a healthy environment and the Islamic, and the dialogue and storytelling, in this way will give a good impact to the growth and development of the child's life, as well as to the level of intelligence and emotional intelligence after birth.